Metabolic profiling and cytotoxic activity of methanol extracts from Chamaecrista duckeana (P. BEZERRA & A. FERN.) H. S. IRWIN & BARNEBY (LEGUMINOSAE, CAESALPINIOIDEAE) - Lima, Daniele Rodrigues de; Franca, Maria Gleiziane de Araujo; Oliveira, Fatima de Cassia Evangelista de; Pessoa, Claudia do O.; Cavalheiro, Alberto Jose [UNESP]; Silva, Maria Goretti de Vasconcelos (Soc Brasileira Quimica, 2022)
The genus Chamaecrista comprises more than 330 species, with only a few studies on their chemical composition and biologic activities. In this study, the phytochemical profile of leaf, stems, and fruits extracts of the C. duckeana were examined by UPLC-ESI-HRMS analysis to determine possibly bioactive constituents. The antioxidant activity was carried out through in vitro assay, by the sequestration of the free radical DPPH. To evaluate the cytotoxic activity of the extracts, an MTT assay was used and the IC50 was determined against HL60 and RAJI cell lines. The metabolic profiles of the botanical parts are dominated by flavonoid class, highlighting isoflavonoids such as daidzin and ononin. All these compounds are reported for the first time in C. duckeana. The extracts presented antioxidant potential, and the activity of the stems extract was higher than the standard butylated hydroxytoluene. In the cytotoxic assay, only HL60 line (leukemia) had growth inhibition over 80%. The stems presented more expressive cytotoxicity with IC50 of 137.3 (104.6-180.1) and 106.8 (96.52-118.3) mu mol. L-1 for HL60 and RAJI, respectively. In conclusion, the present work provides an in-depth knowledge about the chemical profile of C. duckeana, a species rich in bioactive secondary metabolites with cytotoxic activity.
Keywords: Chamaecrista duckeana; UPLC-ESI-HRMS; Cytotoxicity; Isoflavonoids